Mα X-ray emission spectrum of multi-ionized Au atoms - Borovoy, M.O.; Ischenko, R.M.; Shiyanovskiy, V.I. (Functional Materials, 2006)
А model of Mα X-ray emission has been proposed taking into account the main vacancy generation and migration channels within the M shell. Equation have been derived allowing the relative intensity calculation of Mα satellites (S(а). For Au, the Sα values under the Mα spectrum excitation by polychromatic emission of BCV-12 X-ray tubes with Cr and Cu anodes have been studied in experiment. The experimental Sα values coincide (within the error limits) with the calculated ones. The model proposed has been concluded to describe correctly the Mα emission in elements having Z>70.